IoT-Based Smart Parking: Slot Detection and Vehicle Navigation in Parking Buildings - Sapitri, Nurul; Samsumar, Lalu Delsi; Subki, Ahmad (Journal of Computer Science and Informatics Engineering, 2025)
Problems in conventional parking systems are still frequently encountered, such as difficulties in finding vacant slots and the lack of real-time information for drivers. This study aims to develop an IoT-based Smart Parking system capable of detecting parking slot availability and providing automatic voice navigation for drivers within parking buildings. The research method employed is prototyping, consisting of requirement analysis, system design, prototype development, and testing stages. The system utilizes ESP32 as the main microcontroller, infrared and ultrasonic sensors for vehicle detection, and a DFPlayer Mini module for voice navigation. Parking information is displayed in real-time on an LCD screen and the Blynk application via a WiFi connection. The test results show that the system achieved an average response time of 1.57 seconds, an accuracy rate of 94.7%, and stable performance under various test conditions. The components used are cost-effective, with an estimated prototype cost of Rp600,000–Rp1,000,000 per unit, making it feasible for real implementation in parking buildings. The system has proven to be responsive, efficient, and practical, and can serve as an innovative solution for modern parking management based on IoT technology and smart navigation